Ideologi Keluarga Tradisional "IE " dan Kazoku Kokka pada Masyarakat Jepang Sebelum dan Sesudah Perang Dunia II - Anwar, Etty N. (Wacana, Journal of the Humanities of Indonesia, 2007)
In studying Japan's cultural institution, understanding IE, which was the traditional family system used by the Bushi in the Tokugawa era, is indispensable. The IE system is believed to influence the entire aspect of Japanese life, be it the way of thinking, politics, social, economy, marriage, religion, and even the view of "Family State" in the era of Meiji Restoration implemented the structure of IE system. Hence, the IE system is considered to be one of the pillars of Japan's success. This short essay will discuss the IE ideology in the concept of experts on Japanese culture, the principles of Japanese's social relationships, the IE ideology in the structure of "Family State", and Japan's modern family system.